2018
DOI: 10.1101/373704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RNA-binding proteins CELF1 and ELAVL1 cooperatively control RNA isoform production

Abstract: Corresponding authors: LP (Tel +33 22323 4473, luc.paillard@univ-rennes1.fr); and YA (Tel +33 22323 4475, yann.audic@univ-rennes1.fr).Running title CELF1, ELAVL1, and splice isoform production 1 5 10 15 20 ABSTRACT ELAVL1 and CELF1 are RNA-binding proteins that are involved in alternative splicing control. To explore their functional relationship, we looked for mRNAs that are differentially spliced following the depletion of CELF1, ELAVL1, or both. We found that these proteins control the usage of their target… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…CELF1 plays a role in cardiac development, myotonic dystrophy, and cancer 12,13 , but its function in AD has not been elucidated, even though the CELF1 locus has been associated with AD 6,7,8,9 . We found a direct relationship between CELF1 and KLC1 in data obtained by integrating two omics studies that we previously conducted 14,15 . First, transcriptomics data from HeLa cells showed that three of the ten exons most strongly altered by CELF1 knockdown were KLC1 exons (Fig.…”
Section: Celf1 and Klc1mentioning
confidence: 52%
See 2 more Smart Citations
“…CELF1 plays a role in cardiac development, myotonic dystrophy, and cancer 12,13 , but its function in AD has not been elucidated, even though the CELF1 locus has been associated with AD 6,7,8,9 . We found a direct relationship between CELF1 and KLC1 in data obtained by integrating two omics studies that we previously conducted 14,15 . First, transcriptomics data from HeLa cells showed that three of the ten exons most strongly altered by CELF1 knockdown were KLC1 exons (Fig.…”
Section: Celf1 and Klc1mentioning
confidence: 52%
“…As neuronal splicing is especially complex 38 , factors other than CELF1 may also regulate KLC1 splicing, and further studies are needed to fully understand the KLC1 splicing mechanism. In a similar example, the relationship between CELF1 expression and cancer patient survival is variable in different cancer types 14 . When conducting functional genomics for disease research, it is important to confirm the final conclusion of the functional expression analysis at the site of the disease lesion, which in the case of AD is the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CELF1 ( CUGBP Elav-like family member 1 ) gene encodes CELF1 protein, a RNA-binding protein related to the regulation of different post-transcriptional events and alternative splicing, mRNA translation, and mRNA stability ( Beisang et al, 2012 ; Bateman et al, 2017 ). During alternative RNA processing, the protein can select the splicing target site by binding to U/G-rich elements in the transcript sequence, leading to mRNA decay and controlling translation efficiency (preprint David et al, 2020 ). The rs10838725 polymorphism has been associated with LOAD in a GWAS ( Lambert et al, 2013 ; Karch et al, 2016 ; Marioni et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%